2020
DOI: 10.1186/s12893-020-0678-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of score-based prediction of 90-day mortality after liver resection

Abstract: Background: Indications for liver surgery are expanding fast and complexity of procedures increases. Preoperative mortality risk assessment by scoring systems is debatable. A previously published externally validated Mortality Risk Score allowed easy applicable and precise prediction of postoperative mortality. Aim of the study was to compare the performance of the Mortality Risk Score with the standard scores MELD and P-POSSUM. Methods: Data of 529 patients undergoing liver resection were analysed. Mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Compared with the Child-Turcotte-Pugh score, the MELD score was not subject to the subjective influence of ascites and hepatic encephalopathy, and the results were more objective. In addition, MELD can be used to evaluate the survival rate of hepatocellular carcinoma (HCC) patients and surgical risk of patients with cirrhosis [4][5][6][7]. But the reference range of the MELD score is ambiguous, especially in the case of ascites, hepatic encephalopathy, hemorrhage, and Dig Dis 2021;39:258-265 DOI: 10.1159/000511138 other complications in patients with cirrhosis, and the accuracy of prediction is poor [6].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the Child-Turcotte-Pugh score, the MELD score was not subject to the subjective influence of ascites and hepatic encephalopathy, and the results were more objective. In addition, MELD can be used to evaluate the survival rate of hepatocellular carcinoma (HCC) patients and surgical risk of patients with cirrhosis [4][5][6][7]. But the reference range of the MELD score is ambiguous, especially in the case of ascites, hepatic encephalopathy, hemorrhage, and Dig Dis 2021;39:258-265 DOI: 10.1159/000511138 other complications in patients with cirrhosis, and the accuracy of prediction is poor [6].…”
Section: Introductionmentioning
confidence: 99%
“…The MELD has been validated as a score in predicting mortality in patients with liver disease undergoing surgery. Literature suggests that the 30-day mortality increased by 1% for escalating MELD scores between 6 and 20, and an additional 2% per point for scores above 20 [21,22].…”
Section: Qualitative Assessment Of Livermentioning
confidence: 99%
“…A significantly higher risk of PHLF is observed in patients demonstrating 5% or less FLR hypertrophy after embolization [2,3 ▪ ,11 ▪ ,30 ▪ ,37]. Systemic reviews and meta-analyses have shown that patients undergoing resection after PVE demonstrated a significantly lower incidence of PHLF and death in these patients compared with series reporting outcomes after major hepatectomy without PVE [5 ▪▪ ,22,28 ▪▪ ,30 ▪ ,37].…”
Section: Strategies For Functional Liver Remnant Volume Optimizationmentioning
confidence: 99%
“…Furthermore, many authors validate their data with existing scoring systems, which were either not designed exclusively for HR in the first place or derived from different patient profiles [11][12][13]. Hence there is a paucity of data with regard to variables predicting 90-day mortality following elective HR for HCC.…”
Section: Introductionmentioning
confidence: 99%